NORF5/HUG1 Is a Component of the MEC1-Mediated Checkpoint Response to DNA Damage and Replication Arrest in Saccharomyces cerevisiae - Basrai, Munira A. (American Society for Microbiology, 1999)
Analysis of global gene expression in Saccharomyces cerevisiae by the serial analysis of gene expression technique has permitted the identification of at least 302 previously unidentified transcripts from nonannotated open reading frames (NORFs). Transcription of one of these, NORF5/HUG1 (hydroxyurea and UV and gamma radiation induced), is induced by DNA damage, and this induction requires MEC1, a homolog of the ataxia telangiectasia mutated (ATM) gene. DNA damage-specific induction of HUG1, which is independent of the cell cycle stage, is due to the alleviation of repression by the Crt1p-Ssn6p-Tup1p complex. Overexpression of HUG1 is lethal in combination with a mec1 mutation in the presence of DNA damage or replication arrest, whereas a deletion of HUG1 rescues the lethality due to a mec1 null allele. HUG1 is the first example of a NORF with important biological functional properties and defines a novel component of the MEC1 checkpoint pathway.